Aptamer-based multifunctional ligand-modified UCNPs for targeted PDT and bioimaging. Issue 23 (1st June 2018) - Hou, Weijia; Liu, Yuan; Jiang, Ying; Wu, Yuan; Cui, Cheng; Wang, Yanyue; Zhang, Liqin; Teng, I-Ting; Tan, Weihong
Abstract : A multifunctional aptamer-based ligand is designed for the surface modification of UCNPs to build an NIR-triggered PDT nanodrug. Abstract : We designed an aptamer-based multifunctional ligand which, upon conjugation to the surface of upconversion nanoparticles (UCNPs), could realize phase transfer, covalent photosensitizer (PS) loading, and cancer cell targeting in one simple step. The as-built PDT nanodrug is selectively internalized into cancer cells and it exhibits highly efficient and selective cytotoxicity.